A spectrophotometric method for measuring permanganate index (CODMn) by N, N-diethyl-p-phenylenediamine (DPD). (March 2021) - Pang, Zijun; Cai, Yajuan; Xiong, Weihao; Xiao, Junyang; Zou, Jing
Abstract: A new spectrophotometric method for measuring permanganate index (chemical oxygen demand using potassium permanganate (KMnO4 ) as oxidant, CODMn ) in water was established. The method was based on the rapid oxidation of N, N -diethyl- p -phenylenediamine (DPD) by residual KMnO4 in digestion solution under neutral pH condition to form the stable pink radical (DPD ●+ ). Only 20 s were enough to form the pink DPD ●+ . The generated DPD ●+ could be quantitatively measured by a visible spectrophotometer at 551 nm. Stoichiometric coefficient of the reaction between KMnO4 and DPD was close to 1:5 (1:5.07). There was a well linear relationship (R 2  = 0.999) between the change of the absorbance of DPD ●+ at 551 nm and the concentration of CODMn in the range of 0–4.46 mg L −1 . Limit of detection of the DPD method was as low as 0.02 mg L −1 CODMn . The DPD method was highly accurate for measuring CODMn in standard solutions with well recovery rates of 99.17%–102.22%, and was well tolerant to the interference of coexistent Cl − and Fe 3+ . The DPD method was successfully applied for measuring CODMn in real water samples, including surface water, underground water and drinking water. In comparison to the traditional titration method, the proposed DPD method was more convenient to operate, required less samples and digestion reagents (i.e., KMnO4 and H2 SO4 ) and could be employed for online monitor. Graphical abstract: Image 1 Highlights: A convenient, reliable, rapid and eco-friendly method for measuring CODMn is proposed. The DPD method is based on the oxidative coloration of DPD by KMnO4 at neutral pH. Only a very small amount of samples and digestion reagents are needed. The ability to tolerate the coexistent Cl − and Fe 3+ in water samples is strong. It is successful to use this method to measure CODMn in natural water and tap water.